Assessing Causality in Organizational Studies: The Path-Analytic Approach - Neumann, Yoram (Academy of Management Review, 1978)
The article discusses path analysis and relationships between variables in a causal model of organizational theory. Path analysis requires a clear model of relationships and longitudinal research to determine if there are one-way asymetrical relationships or jointly dependent variables—otherwise intervention and change cannot be accurately evaluated. Eight profiles are related to the recursiveness, linearity, and additivity of variables' relationships. The structural-contingency model of organization and individual or group within the organization profile—which have been used in research to explain organizational climate and job satisfaction—are mentioned, as well as three criteria for establishing the validity of a path-analytic approach.